Concordance of imaging modalities and cost minimization in the diagnosis of pediatric choledochal cysts - Murphy, Andrew J. (2012)
PURPOSE: Given evolving imaging technologies, we noted significant variation in the diagnostic evaluation of pediatric choledochal cysts (CDC). To streamline the diagnostic approach to CDC, and minimize associated expenses, we compared typing accuracy and costs of ultrasound (US), intraoperative cholangiography (IOC), and magnetic resonance cholangiopancreatography (MRCP). METHODS: Records of 30 consecutive pediatric CDC patients were reviewed. Blinded to all clinical data, two pediatric radiologists reviewed all US, MRCPs, and IOCs to type CDCs according to the Todani classification. When compared with pathologic findings, the concordance between and accuracy of each diagnostic test were determined. Inflation-adjusted procedure charges and collections for imaging modalities were analyzed. RESULTS: Mean typing accuracy overlapped for US, IOC, and MRCP. Inter-rater reliability was 87 % for US (κ = 0.77), 80 % for IOC (κ = 0.62), and 60 % for MRCP (κ = 0.37). MRCP procedure charges ($1204.69) and collections ($420.85) exceeded IOC and US combined ($264.80 charges, p = 0.0002; $93.40 collections, p = 0.0021). CONCLUSION: Our data support the use of US alone in the diagnosis of pediatric CDC when no intrahepatic biliary ductal dilatation is visualized. However, when dilated intrahepatic ducts are encountered on US, MRCP should be utilized to distinguish a type I from a type IV CDC, which may alter the operative approach.